Photodegradation of trimeprazine triggered by self-photogenerated singlet molecular oxygen - Waseem Ahmad; Mohd. Rehan Zaheer; Anamika Gupta; Jawaid Iqbal (Journal of Saudi Chemical Society)
The antihistaminic drug trimeprazine (1, also known as alimemazine) is photolabile under UV-A light in aerobic conditions. Irradiation of a methanol solution of trimeprazine produces two photoproducts which were isolated as N,N2-trimethyl-3-(10H-phenothiazin-10-yl sulfoxide) propan-1-amine (2) and N,2-dimethyl-3-(10H-phenothiazin-10-yl) propan-1-amine (4). The formation of products was explained by the oxidative photodegradation of trimeprazine in an irreversible trapping of the self-photogenerated 1O2 by the type II photodynamic action of the drug. The generation of singlet oxygen during photolysis of trimeprazine was confirmed by singlet oxygen scavenger 2,5-dimethylfuran (2,5-DMF).